Neural correlates of stimulus-response and response-outcome associations in dorsolateral versus dorsomedial striatum - Stalnaker, Thomas A.; Calhoon, Gwen G.; Ogawa, Masaaki; Roesch, Matthew R.; Schoenbaum, Geoffrey (Frontiers in Integrative Neuroscience, 2010)
Considerable evidence suggests that there is functional heterogeneity in the control of behavior by the dorsal striatum. Dorsomedial striatum may support goal-directed behavior by representing associations between responses and outcomes (R–O associations). The dorsolateral striatum, in contrast, may support motor habits by encoding associations between stimuli and responses (S–R associations). To test whether neural correlates in striatum in fact conform to this pattern, we recorded single-units in dorsomedial and dorsolateral striatum of rats performing a task in which R–O contingencies were manipulated independently of S–R contingencies. Among response-selective neurons in both regions, activity was significantly modulated by the initial stimulus, providing evidence of S–R encoding. Similarly, response selectivity was significantly modulated by the associated outcome in both regions, providing evidence of R–O encoding. In both regions, this outcome-modulation did not seem to reflect the relative value of the expected outcome, but rather its specific identity. Finally, in both regions we found correlates of the available action–outcome contingencies reflected in the baseline activity of many neurons. These results suggest that differences in information content in these two regions may not determine the differential roles they play in controlling behavior, demonstrated in previous studies.